General Theoretical Analysis of the Mechanism of Legal Tax Regulation - PLOTNIKOVA, Kateryna O.; ANANIEVA, Ievgeniia A.; OSYPOV, Dmytro M.; ZAKRYNYTSKA, Victoriia O.; MAKSYMENKO, Natalia O. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
The research is devoted to the detailed analysis of the mechanism of legal tax regulation. The study has found that the mechanism of legal tax regulation is primarily related to the legal regulation of tax debt to ensure its proper execution. Full and timely payment of taxes or fees is meant by proper execution. The implementation of tax debt is defined both in the Basic Law of the state, where the emphasis is placed on the imperative requirement for timely payment of taxes and fees in full, and in the Tax code of Ukraine, which establishes the definition of tax debt as the taxpayer's obligation to calculate, declare and / or pay the amount of tax and fee in the manner and terms determined by the Tax code of Ukraine, customs laws. The analysis of the legislation and the scientific literature has revealed that the most important issue on taxes and fees payment regulation is the establishment of the moment from which the obligation for tax payment arises. Having rights and obligations for a person is another important factor if he becomes a participant in tax relations. The mechanism of legal tax regulation is a set of elements, which are defined in the Tax Code of Ukraine and in accordance with it are divided into basic, additional and optional. The mechanism of legal tax regulation is possible only as a set of basic and additional elements. The absence of at least one of the elements will not allow to legislate a separate tax or levy. The study provides a comprehensive analysis of each element of the tax mechanism.